Dicarboxylate recognition based on ultracycle hosts through cooperative hydrogen bonding and anion–π interactions - Mi, Wen-Hui; Huang, Teng-Yu; Wang, Xu-Dong; Ao, Yu-Fei; Wang, Qi-Qiang; Wang, De-Xian (Beilstein Journal of Organic Chemistry, 2025)
The efficient binding of dicarboxylates represents an important yet challenging issue in supramolecular chemistry. In this study, we designed functional ultracycles as hosts to accommodate large organic dicarboxylate anions. These ultracycles were synthesized via a one-pot strategy starting from macrocyclic precursors. Host–dicarboxylate binding was investigated using 1H NMR titrations, revealing that B4aH exhibits strong binding affinities toward a series of dicarboxylates, with association constants reaching up to 6896 M−1. The selectivity for heptanedioate (C72−) was attributed to cooperative hydrogen bonding, anion–π interactions, and a size-matching effect, as supported by DFT optimizations.
Keywords: anion–π interactions; anion recognition; hydrogen bonding; dicarboxylates; ultracycles